The long adventurous journey of rhombic lip cells in jawed vertebrates: a comparative developmental analysis - Mario F Wullimann; Thomas eMueller; Martin eDistel; Andreas eBabaryka; Benedikt eGrothe; Reinhard W. Köster (Frontiers Media S.A., 2011)
This review summarizes vertebrate rhombic lip and early cerebellar development covering classic approaches up to modern developmental genetics which identifies the relevant differential gene expression domains and their progeny. Most of this information is derived from amniotes. However, progress in anamniotes, particularly in the zebrafish, has recently been made. The current picture suggests that rhombic lip and cerebellar development in jawed vertebrates (gnathostomes) share many characteristics. Regarding cerebellar development, these include a ptf1a expressing ventral cerebellar proliferation (VCP) giving rise to Purkinje cells and other inhibitory cerebellar cell types, and an atoh1 expressing upper rhombic lip giving rise to an external granular layer (EGL, i.e., excitatory granule cells) and an early ventral migration into the anterior rhombencephalon (cholinergic nuclei). As for the lower rhombic lip (LRL), gnathostome commonalities likely include the formation of precerebellar nuclei (mossy fiber origins) and partially primary auditory nuclei (likely convergently evolved) from the atoh1 expressing dorsal zone. The fate of the ptf1a expressing ventral LRL zone which gives rise to (excitatory cells of) the inferior olive (climbing fiber origin) and (inhibitory cells of ) cochlear nuclei in amniotes, has not been determined in anamniotes. Special for the zebrafish in comparison to amniotes is the predominant origin of anamniote excitatory deep cerebellar nuclei homologues (i.e., eurydendroid cells) from ptf1a expressing VCP cells, the sequential activity of various atoh1 paralogues and the incomplete coverage of the subpial cerebellar plate with proliferative EGL cells. Nevertheless, the conclusion that a rhombic lip and its major derivatives evolved with gnathostome vertebrates only and are thus not an ancestral craniate character complex is supported by the absence of a cerebellum (and likely absence of its afferent and efferent nuclei) in jawless fishes.